2014
DOI: 10.1063/1.4890822
|View full text |Cite
|
Sign up to set email alerts
|

The scaling of weak field phase-only control in Markovian dynamics

Abstract: We consider population transfer in open quantum systems, which are described by quantum dynamical semigroups (QDS). Using second order perturbation theory of the Lindblad equation, we show that it depends on a weak external field only through the field's autocorrelation function, which is phase independent. Therefore, for leading order in perturbation, QDS cannot support dependence of the population transfer on the phase properties of weak fields. We examine an example of weak-field phase-dependent population … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…For example, can population transfer from a ground to the excited surface be phase-controlled for a dye molecule in solution? While this has theoretically been shown to be impossible if the time evolution is Markovian [213], most solvents lead to non-Markovian system dynamics.…”
Section: State Of the Artmentioning
confidence: 99%
“…For example, can population transfer from a ground to the excited surface be phase-controlled for a dye molecule in solution? While this has theoretically been shown to be impossible if the time evolution is Markovian [213], most solvents lead to non-Markovian system dynamics.…”
Section: State Of the Artmentioning
confidence: 99%
“…5 Properties of interference have been used to devise strict conditions on the possibility of coherent control in a variety of scenarios. [6][7][8][9][10][11][12] These conditions have an important role in informing the interpretation of coherent control experiments.…”
mentioning
confidence: 99%
“…Recently, Kukura et al failed to reproduce earlier results using a methodology which, in principle, should eliminate any non-phase effects. 32 Steady-state onephoton phase control has been shown to be impossible for certain classes of open quantum systems, 9 as it is for closed systems. 7 In addition, it has been demonstrated that multiphoton effects can create large contribution even in the linear absorption regime, 14,[33][34][35] which might lead to multiphoton phase control in seemingly one-photon experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 Note also that previous work suggests that the possibility of weak-field control is destroyed by the Markov approximation. 30,34 In this exploratory study, we want to investigate whether pure energy dissipation can lead to phase control in the weak-field limit. To that end, we start from the Time-Dependent Hartree (TDH) approximation for the system-bath coupling which is also often referred to as the Time-Dependent-Self-Consistent-Field (TDSCF) approximation.…”
mentioning
confidence: 99%